ANALISIS PERAN PEMUDA DALAM RAGAM ORGANISASI PADA KOMITE NASIONAL PEMUDA INDONESIA KALIMANTAN TENGAH DALAM PEMBANGUNAN DAERAH DI KALIMANTAN TENGAH - Indah Tri Handayani; Milka Milka; Mambang Tubul (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
Youth is one of the pillars that has a big role in the journey of the life of the nation and state so that the progress of a country is more or less determined by the thoughts and active contributions of youth in the State of Indonesia. Likewise in the scope of social life, youth is a potential identity in the community structure as the successor to the nation's struggle and a human resource for development, because youth as the hope of the nation can be interpreted that whoever controls youth will control the future. This research is expected to provide an overview of youth in youth organizations in Central Kalimantan in the development process, especially in the city of Palangka Raya. In addition, this paper is also expected to be a motivation for young people to take part in the regional development process. Therefore, it is very important to see an overview of the function and role of youth in regional development through the Central Kalimantan Indonesian Youth National Committee which accommodates it. So that this research becomes interesting to review considering that the results of this study will analyze how the participation of youth in the sustainability of the development of the Central Kalimantan Region will be.